Effective Learning Strategies for Qur'anic Sciences and Tafsir in the Education of Ulama Cadres at MUI in Bogor, Cianjur, and West Java - Asep Ahmad Fathurrohman; Acep Dani Ramdani (PALAPA, 2024)
This research aims to evaluate the teaching and learning of Qur'anic Sciences and Tafsir in the Pendidikan Kader Ulama (PKU) program at the MUI in Bogor, Cianjur, and West Java. The research method used is a qualitative approach with data collection techniques consisting of interviews, observations, and document analysis. The findings indicate variations in the evaluation process across different regions, including methods such as paper tests, question-and-answer sessions, and practical assessments. Additionally, the evaluation in Bogor tends to focus on cognitive aspects, while in Cianjur and West Java, cognitive, affective, and psychomotor elements are assessed. This study contributes important insights into more effective learning strategies by applying Multiple Intelligences theory, allowing each participant to learn according to their unique intelligence. Therefore, this research is expected to provide input for the development of a more inclusive and adaptive PKU program.